2009
DOI: 10.1016/j.adolescence.2009.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with deliberate self‐harm behaviour among depressed adolescent outpatients

Abstract: This study examined whether depressed adolescent outpatients with deliberate self‐harm behaviour (DSH) differed from non‐suicidal depressed adolescent outpatients in depressive and anxiety symptoms, alcohol use, perceived social support and number of negative life‐events. Depressed adolescent outpatients (n = 155) aged 13–19 years were interviewed using K‐SADS‐PL for DSM‐IV Axis I diagnoses and completed self‐report questionnaires. Suicidal behaviour was assessed by K‐SADS‐PL suicidality items. Depressed adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 42 publications
5
24
0
1
Order By: Relevance
“…This finding supports previous studies that have found social support to be a protective factor against suicidality [5759], particularly perceived parental support [57, 58]. …”
Section: Discussionsupporting
confidence: 91%
“…This finding supports previous studies that have found social support to be a protective factor against suicidality [5759], particularly perceived parental support [57, 58]. …”
Section: Discussionsupporting
confidence: 91%
“…Two cross-sectional studies included direct comparisons of individuals who engaged in NSSI and had no history of suicidality with suicidal counterparts (Baetens, Claes, Muehlenkamp, Grietens, & Onghena, 2011; Tuisku et al, 2009). One of these studies reported no difference between the two groups (OR = .55 [95% CI = .22–1.40]; Tuisku et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…One of these studies reported no difference between the two groups (OR = .55 [95% CI = .22–1.40]; Tuisku et al, 2009). This finding should be interpreted with some caution, however, given its relatively small sample size (n NSSI only = 21, n NSSI and suicidality = 52), which limits its ability to detect a significant effect.…”
Section: Resultsmentioning
confidence: 99%
“…NSSI is often repetitive with varying degrees of severity (Tuisku et al, 2009). Although related, non-suicidal and suicidal self-injury are conceptualized as overlapping, but distinct, clinical phenomena (Wichstrøm, 2009).…”
Section: Introductionmentioning
confidence: 99%